Assessment of Glaucomatous Changes in Subjects with High Myopia Using Spectral Domain Optical Coherence Tomography - Shoji, Takuhei; Sato, Hiroki; Ishida, Masahiro; Takeuchi, Masaru; Chihara, Etsuo (Investigative ophthalmology & visual science, 2011)
To evaluate the diagnostic ability to detect glaucoma in highly myopic eyes using spectral domain-optical coherence tomography (SD-OCT) parameters in a cross-sectional comparative study. A total of 82 patients with high myopia (≤-5 D) presented between April 2008 and August 2009. Subjects comprised 31 participants with high myopia but not perimetric glaucoma (no glaucoma group) and 51 patients with high myopia and concomitant perimetric glaucoma (glaucoma group). Ganglion cell complex (GCC), circumpapillary retinal nerve fiber layer (p-RNFL), and disc configuration parameters were obtained from algorithms of the SD-OCT system and subsequently compared. Receiver operating characteristics curves were constructed for each measurement parameter, and areas under the curves (AUCs) were compared. All optic nerve fiber head, except disc area, and GCC parameters differed significantly between groups (P < 0.05). The largest AUCs from disc configuration, circumpapillary RNFL, and GCC parameters were 0.844 (C/D vertical), 0.826 (RNFL average), and 0.954 (global loss volume [GLV]), respectively. GLV was significantly better for detecting perimetric glaucoma than both the C/D vertical and RNFL average (P < 0.05). All algorithms of the OCT system were useful for discriminating glaucoma. Among these, GCC measurements offered the best parameters for the clinical diagnosis of glaucoma in patients with high myopia and concomitant perimetric glaucoma.